Índice de qualidade da dieta de adolescentes e fatores associados - Wendpap, Loiva Lide (2012)
Introduction: To assess the diet quality of adolescents is useful in the development of nutritional health indicators. Objective: To evaluate the diet quality and its association with socio-demographic and lifestyle variables, and nutritional status of adolescents. Methods: Cross-sectional study, that is a sub-sample of a cohort study with 1326 adolescents aged 10 to 14 years, of both sex, students of public and private schools of the urban area of Cuiabá City, Mato Grosso State, Brazil, between 2009 and 2011. Data were collected based on a questionnaire administered by an interviewer, and information on food intake was obtained using a food frequency questionnaire. The diet quality was assessed by the Diet Quality Index Revised, adapted to the Brazilian population. This index is composed of scores distributed by the components that characterize the different aspects of diet, and the maximum value of 100 points indicates high quality diet. The score of components was expressed in mean and confidence interval of 95%. The chi-square test was used to evaluate the association between the Diet Quality Index Revised and independent variables. Variables with p-value ≤ 0.20 in the bivariate analysis were included in the logistic regression analysis. In all analyses, the significance level of 5% was used. Results: The mean of the Diet Quality Index Revised was 75.14 points (CI 95%: 74.82- 75.46). The means for the components “Dark Green, Orange Vegetables and Legumes” (2.68); “Milk and Dairy Products” (5.85) and “Sodium” (4.53) were low. Higher scores of diety quality were associated with: low time (≤ 2 hours / day) spent on sedentary activities like watching television or using computer / games (OR 1.33; CI 95%: 1.01-1.74); longer time (≥ 300 minutes / week) of physical activity (OR 1.38; CI 95%: 1.07-1.78) and overweight (OR 1.67; IC 95%: 1.28-2.19). Conclusion: Healthy lifestyle, characterized by regular exercise and low level of sedentary activities was associated with better diet quality. Therefore the importance of encouraging physical activity, reducing the number of daily hours in sedentary activities and intervening in eating habits of adolescents are highlighted.